1996
DOI: 10.1111/j.1432-1033.1996.0713h.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triacylglycerol Transfer Protein Prevents Presecretory Degradation of Apolipoprotein B‐100

Abstract: The role of microsomal triacylglycerol transfer protein (MTP) in the secretion of apolipoprotein B-1 00 (apoB-100) has been studied using an inhibitor of MTP: 4'-bromo-3'-methylmetaqualone. In vitro, this compound inhibits trioleoylglycerol transfer between lipid vesicles mediated by MTP with an IC,, of 0.9 pM whereas it does not inhibit the lipid transfer mediated by the cholesteryl ester transfer protein.In HepG2 cells, 4'-bromo-3'-methylmetaqualone inhibits the secretion of apoB-100 with an IC,, of 0.3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…This compound inhibited secretion of apoB100 in a dose-dependent manner but had no effect on secretion of other proteins from HepG2 or primary human hepatocytes (41). As shown in Fig.…”
Section: Fast Inhibition Of Apob100 Production By An Mtp Inhibitor-prmentioning
confidence: 66%
See 2 more Smart Citations
“…This compound inhibited secretion of apoB100 in a dose-dependent manner but had no effect on secretion of other proteins from HepG2 or primary human hepatocytes (41). As shown in Fig.…”
Section: Fast Inhibition Of Apob100 Production By An Mtp Inhibitor-prmentioning
confidence: 66%
“…we demonstrated that 4Ј-bromo-3Ј-methylmetaqualone specifically inhibited MTP-mediated lipid transfer (41). This compound inhibited secretion of apoB100 in a dose-dependent manner but had no effect on secretion of other proteins from HepG2 or primary human hepatocytes (41).…”
Section: Fast Inhibition Of Apob100 Production By An Mtp Inhibitor-prmentioning
confidence: 79%
See 1 more Smart Citation
“…In Chinese hamster ovary cells, in addition to MTP, cholesterol 7 ␣ -hydroxylase has been shown to be necessary for apoB secretion (54). Third, the importance of the lipid transfer activity in the lipidation of apoB polypeptides was reinforced by using specific inhibitors (55)(56)(57)(58)(59)(60). MTP inhibitors that inhibited lipid transfer activity in vitro decreased apoB secretion in vivo.…”
Section: Role Of Mtp's Lipid Transfer Activity In Lipoprotein Assemblymentioning
confidence: 99%
“…Once inside the enterocyte, the lipolytic products are bound to cytoplasmic FABPs (I-and L-FABP) in order to migrate to the ER where they are reesterifi ed by various enzymes: monoacylglycerol acyltransferase (MGAT) and diacylglycerol acyltransferase (DGAT) for the conversion of 2-MG to TG, ACAT-2 for the esterifi cation of(Ping Pong Bi Bi kinetics), MTP acts as a carrier of lipids from their site of synthesis to nascent lipoproteins within the ER ( 66 ). Additional evidence for the critical role of MTP in CM and VLDL production in the enterocyte and hepatocyte, respectively, has been provided with pharmacological approaches utilizing specifi c MTP inhibitors that simultaneously inhibit lipid transfer activity in situ while blocking Apo B secretion (67)(68)(69)(70). Treatment with MTP inhibitors results in a dose-dependent decrease in Apo B secretion, suggesting that MTP is rate-limiting for TG-rich lipoprotein secretion ( 67 ).…”
mentioning
confidence: 99%